COMPOUND WORDS IN ENGLISH - Christianto, Danin (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2020)
Language is a means of communication which is used by living beings to communicate with each other. There are many important components in language to create a successful communication, such as sound, sentence, meaning, and etc. One of the components is word. Word can be considered as a complex part in language since it has many different forms. Compound word, for example, is a word which is formed through one of the word-formation processes by combining one lexical item with another and thus produces a new word with a new meaning. This paper investigates the types of English compounds and the lexical categories which are resulted from the process of compounding. The first results showed that the types of English compounds are endocentric, exocentric, and copulative compounds. The second results showed that the lexical categories resulted from the process of compounding are noun compound, verb compound, and adjective compound. Based on the results, the researcher hopes that readers can gain deeper insight and knowledge on English compound words.